A sandwich ELISA to detect VHSV and IPNV in turbot - Vázquez Brañas, M.; Coll Morales, Julio; Estepa, A. (Aquaculture International, 1994)
The recent demonstration that reared turbot (Scophthalmus maximus L) is a natural host for salmonid rhabdoviruses has made their rapid detection relevant to these fish species. A unique protocol to select and use non-competitive monoclonal antibodies (Mabs) for two high-sensitivity sandwich ELISAs has been developed to detect both infectious pancreatic necrosis virus (IPNV) and viral haemorrhagic septicaemia virus (VHSV) in turbot kidney extracts to assess the possibility of using them in field diagnosis. For maximum sensitivity, turbot kidney extracts can be two-fold diluted with high-ionic strength buffers and assayed for the presence of the major viral proteins (VMS rhabdovirus nucleoprotein N/Nx and/or IPN birnavirus protein VP3). The use of control plates coated with irrelevant mouse antibodies (IgG1 and IgG2a) in parallel ELISAs allows for a precise estimation of possible false positives. Turbot kidney extracts with low levels of virus might now be assayed directly without using cell culture, with high precision and in a short time during the acute phase of these viral diseases in reared turbot. © 1994, Chapman & Hall. All rights reserved.